Die ontstaan en inrigting van die SVTT (Praktiese Opleiding) van die Nederduitsch Hervormde Kerk van Afrika aan die Universiteit van Pretoria - Beukes, M. J. du P. (Hervormde teologiese studies, 1992)
The inception and establishment of the Centre for Continued Theological Education (Practical Training) of the Nederduitsch Hervormde Kerk van Afrika at the University of Pretoria During 1988 the Curriculum Committee of the Faculty of Theology (Sec A) launched an in-depth investigation into the training of ministers of the Nederduitsch Hervormde Kerk van Afrika. With a view to maintaining the practical and academical training standards, it was decided to provide for more practical training to take place at the Centre for Continued Theological Education (CCTE). During 1989 this decision culminated in a second division of the CCTE which started to provide this important supplement to the existing curriculum, known as Practical Training. This division has since been called the CCTE (Practical Training) Department.